LEISURE INDUSTRY AND ITS VALUE FOR REGIONAL SOCIO-ECONOMIC DEVELOPMENT - GUSEVA, Nataliya (Ekonomichna ta Sotsialna Geografiya, 2016)
Free time and forms of its spending, rather than material things, increasingly become one of the central values of the modern person. Researchers use different terms to define free time: leisure, recreation, entertainment, etc. Leisure is an inherent component of a person vital activity, and leisure industry became one of the most profitable types of economic activity. Thus leisure industry should become the prior economic sector in our country and needs more detail research.Leisure industry consists of the set of different business entities (leisure institutions) providing services aimed at fulfilling person’s needs in free time from work. The institutions list of leisure industry is quite big. It causes the necessity of their classification. Therefore, by the level of involvement in leisure activities all leisure institutions are divided into 3 groups, providing leisure services as an additional, main or peripheral activity respectively. Among institutions providing leisure services as the main activity, functional sub-groups are sports, entertainment, cultural, educational, and spectator institutions. Other classification criteria are visitor’s age, administrative-territorial status, accessibility, period of functioning, ownership, capacity, cost, service level, establishment time, visitor behavior, etc.Leisure industry has significant influence on economic and social development of a country and its regions.

Однією з центральних цінностей сучасної людини дедалі більше стають не матеріальні речі, а вільний час, форми його проведення. Для позначення вільного часу дослідники використовують різні поняття – дозвілля, відпочинок, розваги, рекреація тощо. Дозвілля є невід’ємною складовою життєдіяльності людини, а індустрія дозвілля перетворилась у найбільш прибутковий вид економічної діяльності. З огляду на це, індустрія дозвілля в нашій країні має стати пріоритетною сферою економіки та потребує ретельного дослідження.Індустрія дозвілля представляє собою сукупність різних суб’єктів господарської діяльності (закладів дозвілля), які надають послуги, спрямовані на задоволення потреб людини у вільний від роботи час. Перелік закладів, що можна віднести до індустрії дозвілля, досить значний. Це обумовлює необхідність їх класифікації. Так, за рівнем залученості до дозвіллєвої діяльності всі заклади дозвілля поділяються на 3 групи – заклади, для яких дозвілля є додатковою, основною та побічною діяльністю. Серед закладів, для яких дозвілля є основною діяльністю, за функцією виділяють спортивні і спортивно-видовищні, розважальні, культурно-просвітницькі, видовищні заклади. Іншими класифікаційними критеріями закладів дозвілля є вік відвідувачів, адміністративно-територіальний статус, доступність, термін дії, форма власності, місткість, вартість, рівень сервісу, період виникнення, поведінка відвідувачів тощо.Індустрія дозвілля має важливий вплив на економічний та соціальний розвиток країни та її регіонів.
ІНДУСТРІЯ ДОЗВІЛЛЯ ТА ЇЇ ЗНАЧЕННЯ ДЛЯ СОЦІАЛЬНО-ЕКОНОМІЧНОГО РОЗВИТКУ РЕГІОНУ
Keywords: free time; leisure; leisure types; leisure industry; leisure industry structure; leisure institutions; classification of leisure institutions; вільний час; дозвілля; види дозвілля; індустрія дозвілля; структура індустрії дозвілля; заклади дозвілля; класифікація закладів дозвілля